Quantifying effect of concurrent draw on extraction zones in in block caving mines using large scale 3D physical model - Halim, Adrian; Trueman, R.; Castro, Raul (Maney Publishing, 2008)
There remains a debate within the literature and among practitioners of caving methods as to the effect on draw zone geometry for the concurrent drawing of multiple drawpoints. Concurrent draw refers to an extraction schedule where a limited amount of material is drawn from each drawpoint before moving to the next drawpoint to draw the same amount. One hypothesis concludes that the flow geometries of a single drawpoint increase while another assumes no change from that of isolated draw. The largest 3D physical model constructed using gravel as the model media has been used to further investigate interactive draw of extraction zones as part of an International Caving Study (ICS) and Mass Mining Technology Project supported by major international companies with interest in caving methods. All extraction zones were measured in 3D. To date a maximum of 10 drawpoints have been modelled. Model results so far indicate no growth in the horizontal width of extraction zones using concurrent draw. Experiments conducted with multiple drawpoints that were spaced less than the width of isolated extraction zones showed that the combined horizontal area of draw appears to reduce with the increasing overlap of isolated extraction zones. The horizontal widths of extraction zones continued to increase within the height of the draw tested.